The Mental Health Status of Students of Medicine and Dentistry A Study in Shahid Sadoughi University of Medical Sciences Yazd Iran - Mehdi Tabrizizadeh; Seyed Mojtaba Yasini Ardakani; Parvaneh Rostamzade; Meysam Zare (Kerman University of Medical Sciences, 2013)
Background & Objectives: Mental health is one of the most important issues in various populations specially the student populations which by itself can provide a background for academic achievement or failure The aim of the present study was to investigate the mental health status of students of medicine and dentistry in Shahid Sadoughi University of Medical Sciences Yazd Iran Methods: This descriptiveanalytic and crosssectional study was performed in the academic year of 20092010 according to the Symptom Checklist90 (SCL90) test 232 questionnaires containing demographic and SCL90 questions were distributed among the systematically selected students of medicine and dentistry in Shahid Sadoughi University of Medical Sciences Data were analyzed using chisquare test Results : 132 students (691%) had no mental disorder while 53 (277%) had slight and 6 (32%) had moderate mental disorders The rate of severe mental disorders was zero The most commonly observed mental disorders were paranoia in 108 students (565%) sensitivity in mutual relations in 82 students (44%) and obsessive compulsive disorder in 79 students (414%) None of the demographic variables showed significant statistical relation with mental health status Conclusion: The obtained rate for suspicious cases of mental disorders in students of medicine and dentistry requires more attention in offering health consulting services for them in order to solve their psychiatry problems